Toward Health System Recovery in the Aftermath of Ebola Outbreak in Guinea: New Approaches for Improved Knowledge of Target Populations at the Community Level - Mandy Kader Konde; Balla Moussa Kéita; Lansana Massandouno; Abdourahamane Diallo; Mamadou Diallo; Mamadou Alimou Toure; Alkhassim Amadaye; Alioune Camara; Cisse Fode; Alexandre Delamou; Abdoul Habib Beavogui; Ndiouga Diallo; et al. (SAGE Publishing, 2022)
Background: Before the COVID-19 pandemic, Guinea has been the epicenter of the huge West Africa Ebola outbreak (2014-2016), that impact heavily the health system. Demographic information is one of the most basic data sources for health systems and services delivery, and yet can be very difficult to obtain with any accuracy. The objectives were to contribute among other to: (i) a determination of the catchment area (health coverage area and responsibility) of the Kirikilan health facility (PCM); (ii) geocoded mapping to find out exactly where these populations per sector of Kirikilan neighborhood lives; (iii) an approach for regular and systematic annual demographic follow up of target populations. Methods: The study was a 3-year community-based survey with annual follow up of the population within the quartier of Kirikilan in Dubreka Prefecture in Guinea. It was an exhaustive enumeration of the population, sector by sector of the quartier, then there was no sampling size neither estimation. Results: In October 2017 as a baseline of the study, the enumeration showed the total population was 8824 persons, 936 compounds, 1435 households, and the breakdown by sub quartier (sector) has been performed. It's showed the interest of the mapping of the target populations with geo-referenced localization. The annual follow up by demographic enumerus showed a dramatic increase of the size of the population, including strong migration of the evicted population due to urbanization purpose in some districts of Conakry, the capital. Conclusion: The study showed the importance of the enumeration and follow up of the target populations, but also of the setting up community data based to improve the district health information system (DHIS 2) in Guinea. The approach has a best practice could be an importunity to improve data sharing, mapping, health quality access, and affordability for a sustainable health toward universal health coverage.